Exploration of Bone Alterations in Gaucher Disease Type 1: A Global and Systematic Analysis of Scientific Knowledge - Daniela Arturo-Terranova; Lina Johanna Moreno Giraldo; José María Satizabal Soto (Journal of Inborn Errors of Metabolism and Screening)
Abstract Gaucher disease type 1 (GD1) is the most common lysosomal storage disorder, characterized by hepatomegaly, splenomegaly, anemia, thrombocytopenia, and skeletal manifestations, which significantly affect quality of life. This systematic review aimed to assess the current state of the disease, focusing on skeletal manifestations. A systematic search was conducted between 2000 and February 2024 in multiple languages using PRISMA-ScR and JBI methods. A total of 96 studies were identified: 23 systematic reviews, 23 descriptive studies, 17 case reports, 13 experimental studies, 10 retrospective studies, 4 observational studies, 4 prospective studies, and 2 cross-sectional studies. The highest number of articles on the topic was published in 2015, and the countries with the most publications were the USA, Italy, Brazil, and Argentina over the 23 years covered in the search. These studies cover various aspects of GD1, including skeletal features, patient phenotypes, clinical annotations, diagnostics, therapies, and patient perspectives. Despite advances, challenges such as disease heterogeneity and inconsistent results persist. This review underscores the importance of further research to improve understanding and management of GD1, with an emphasis on skeletal manifestations.